Band structure engineering of multiple band degeneracy for enhanced thermoelectric power factors in MTe and MSe (M = Pb, Sn, Ge). Issue 112 (27th October 2015) - Ding, Guangqian; Li, Jie; Gao, Guoying
Abstract : The thermoelectric power factor (PF) can be improved by the band structure engineering of multiple band degeneracy. Abstract : The thermoelectric (TE) conversion efficiency is always limited by a low TE figure of merit ( ZT ). Improving ZT requires both a high power factor (PF) and a low thermal conductivity. So far, however, most efforts to improve ZT have been made by reducing the thermal conductivity rather than maximizing the PF. Recently, band engineering which can effectively solve the paradox between the density-of-states effective mass and carrier mobility, has been treated as an efficient approach to improve ZT by maximizing the PF. In this paper, based on first-principles and the Boltzmann transport theory, we calculate the electronic structure and thermoelectric properties of classical IV–VI semiconductors MTe and MSe (M = Pb, Sn, Ge). We find that band engineering of multiple band degeneracy induced by engineering the conduction bands near the Fermi level can increase the room temperature n-type PF around 3 to 8 times. The present work is useful in thermoelectrics and will attract more research interest in optimizing the TE performance by band engineering.